2014
DOI: 10.1038/aps.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles: new light shed on the understanding of venous thromboembolism

Abstract: Microparticles are small membrane fragments shed primarily from blood and endothelial cells during either activation or apoptosis. There is mounting evidence suggesting that microparticles perform a large array of biological functions and contribute to various diseases. Of these disease processes, a significant link has been established between microparticles and venous thromboembolism. Advances in research on the role of microparticles in thrombosis have yielded crucial insights into possible mechanisms, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 94 publications
(113 reference statements)
1
20
0
Order By: Relevance
“…The increased incidence of venous thrombosis throughout the course of GBM has been well documented (38). In fact, the elevated levels of circulating MVs in cancer patients has been correlated with thrombosis in a number of cancer types (9,11,30). However, it has previously been demonstrated that elevated levels of TF-positive MVs do not correlate with thrombosis occurrence in patients with GBM (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased incidence of venous thrombosis throughout the course of GBM has been well documented (38). In fact, the elevated levels of circulating MVs in cancer patients has been correlated with thrombosis in a number of cancer types (9,11,30). However, it has previously been demonstrated that elevated levels of TF-positive MVs do not correlate with thrombosis occurrence in patients with GBM (39).…”
Section: Discussionmentioning
confidence: 99%
“…Increased TF expression has been also associated with cancer-associated thrombosis, a highly relevant systemic response (8,9). In fact, several studies suggest that circulating extracellular vesicles containing TF may be important in a patient's prothrombotic state (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Further, although rates of VTE are heavily debated, autopsies have shown pulmonary embolism (PE) rates up to 35% (38) and PE-related mortality rates as high as 40% (11). Microparticles are known contributors to hypercoagulability in various disease processes (18, 19, 39), and previous research has demonstrated that PMPs are associated with increased procoagulant activity in fresh frozen plasma (40) and are associated with hypercoagulability in other injury models (22). The current study is the first to highlight the link between PMPs and coagulation in burns and future burn care may require targeted anticoagulation strategies based on the time course after injury, including use of agents that target platelets and PMPs specifically, to more effectively prevent thrombosis-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these conditions are characterized by a hypercoagulable state, which may lead to venous thrombosis. Indeed, the direct link between MPs and VTE is supported by a considerable amount of new evidence [24,25,27]. MPs may become in the future one of the novel biomarkers for early primary and/or secondary VTE prevention protocols [28].…”
Section: Introductionmentioning
confidence: 99%